2012
DOI: 10.1155/2012/128965
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Roles of Tumour Necrosis Factor-Alpha in Prostate Cancer Biology

Abstract: Tumour necrosis factor (TNF) is a pleiotropic cytokine with dual roles in cancer biology including prostate cancer (PCa). On the one hand, there is evidence that it stimulates tumour angiogenesis, is involved in the initiation of PCa from an androgen-dependent to a castrate resistant state, plays a role in epithelial to mesenchymal plasticity, and may contribute to the aberrant regulation of eicosanoid pathways. On the other hand, TNF has also been reported to inhibit neovascularisation, induce apoptosis of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 65 publications
(86 reference statements)
1
55
1
1
Order By: Relevance
“…However, the higher amounts initiate tumor cell death and stimulate the antitumor response (Tse et al 2012). It is believed that chronic inflammation is one of the main risk factors for the development of carcinogenesis process, in which TNF-α plays an extremely important role.…”
Section: Tnf-α In Cancer and Cancerogenesismentioning
confidence: 99%
“…However, the higher amounts initiate tumor cell death and stimulate the antitumor response (Tse et al 2012). It is believed that chronic inflammation is one of the main risk factors for the development of carcinogenesis process, in which TNF-α plays an extremely important role.…”
Section: Tnf-α In Cancer and Cancerogenesismentioning
confidence: 99%
“…Interactions between tumor-derived IL-6 and TAMs-derived TNF-α enhanced incidence of prostate cancer metastases both to the bones and regional lymph nodes [314]. Moreover, prostate tumors have been characterized by increased TNF-α, TNFR1, and TNFR2 levels, which correlated with poor prognosis [315].…”
Section: Inflammation and Cancer Escapementioning
confidence: 99%
“…Among them, recombinant human tumour necrosis factor alpha (rhTNFa) is one of the most investigated biomarkers because several studies demonstrated its potential application in diagnostic and therapeutic applications [8][9][10]. Indeed, rhTNFa is an inflammatory cytokine mainly secreted in response to a diverse range of stresses [8,9], overexpressed in the microenvironment of many tumours and responsible, in most cases, for their progression [11,12].…”
Section: Introductionmentioning
confidence: 99%